Moiyabana Earthquake in Botswana during 2017: Foreshocks and Aftershocks Effects - Thebeetsile A. Olebetse; Matlhogonolo L. Mmese; Rapelang E. Simon; Joseph Maritinkole (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 1, 2022)
An Mw 6.5 earthquake occurred in Moiyabana, central Botswana on April 3, 2017. This chapter expands on our previous paper on this subject, and highlights on the effects of the spatial distribution of foreshock and aftershock sequences associated with this earthquake. The data used was from the Botswana Geoscience Institute (BGI) and was analysed with the Seisan software. The Moiyabana earthquake was preceded by foreshocks that were widespread across the country and had no preferred orientation. The closest foreshock to this earthquake was at a distance of 50 km. This foreshock had an epicentre located at 22.10 oS, 25.40oE and it occurred along the boundary between the Zimbabwe craton and Limpopo mobile belt on March 14, 2017. The aftershocks cluster displays a northwest-southeast trend with a length of 47 km, most likely indicating the rupture plane. Most of these aftershocks have focal depths shallower than 15 km and are clustered around the boundary between the Kaapvaal craton and Limpopo mobile belt. The largest aftershock was located at 22.55 oS, 25.06oE and occurred two days after the mainshock with a local magnitude of 5.3. The farthest aftershock occurred more than 200 km away from the mainshock along the Zimbabwe craton-Limpopo mobile belt margin. The mean and variance of the difference between the largest aftershock and aftershock magnitude for all events is 1.26 +/- 0.14, and closely matches with that from Båth’s law within uncertainties. We infer that the foreshocks and aftershocks of the Moiyabana earthquake mark off the margins of the cratonic units from the mobile belt.